Imaging biomarkers in the hyper-acute phase following traumatic brain injury - Lawrence, T (2018)
Traumatic brain injury is a leading cause of death and disability worldwide. There is huge variability in clinical outcome results, due to broad heterogeneity in injury patterns as well as unidentified progression of the secondary injury cascade. Conventional assessment tools used in clinical practice (computed tomography and Glasgow Coma Scale) often fail to reflect the true severity of injury, limiting the application of treatment interventions that may improve long-term clinical outcome. In this thesis, I investigated the potential for advanced magnetic resonance imaging (MRI) to identify injury severity and predict long-term clinical and cognitive outcome after traumatic brain injury. Eighteen patients with a range of injury severities were studied longitudinally using MRI within the first few hours following trauma (the hyper-acute phase) and again at both 7-15 days and 6-9 months. In comparison to healthy controls, patients showed evidence of diffuse microhaemorrhage, biochemical disruption and axonal injury within the hyper-acute phase following trauma that localised to regions of susceptibility and reflected injury severity and progression over 7-15 days (acute phase). Furthermore, MRI markers were correlated with subsequent clinical outcome at 6-9 months (chronic phase). Finally, disruption to a key functional network, the so-called ‘default mode network’, was evident in the hyper-acute phase and reflected injury severity and long-term outcome. These findings suggest crucial clinical applications for MRI markers acquired in the immediate post-injury period to improve the classification of patients’ injury severities and identify patients who are likely to develop functional deficits that limit their long-term recovery.